PENDAMPINGAN KEGIATAN EDUPRENUER PESERTA DIDIK MELALUI PELATIHAN ECOPRINT TOTEBAG DI PKBM MERCUBUANA - Sari Lehot, Benedikta; Sasabilla, Devi Amanda; Adelia Saydina, Cindy; Fakiroh, Dzakiyatul; Nur Oktaviani, Rizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This activity focused on developing the entrepreneurial spirit of students at the Mercu Buana Community Learning Center (PKBM) through a workshop on making ecoprint tote bags. The edupreneur concept was implemented to integrate entrepreneurial elements into education to foster independence, creativity, and practical skills. Through structured training and mentoring methods (planning, implementation, and evaluation), students were taught the theory of natural materials and the practical application of producing bags that are market-competitive. This activity successfully enhanced students' creativity, production skills, and insight into environmentally friendly business opportunities. Other positive impacts were seen in increased learning motivation, independence, and interest in entrepreneurship. Therefore, the ecoprint tote bag training at PKBM Mercu Buana has proven effective as a mentoring tool for edupreneurs, equipping students with practical and sustainable entrepreneurial skills.